1998
DOI: 10.1007/bf03161444
|View full text |Cite
|
Sign up to set email alerts
|

Sediment chemistry associated with native and non-native emergent macrophytes of a Hudson River marsh ecosystem

Abstract: In tidal freshwater marshes of the Hudson River, coverage by Phragmites australis and Lythrum salicaria has increased greatly over the past twenty years, although Typha angustifolia is still the predominant vegetation. Prior to any attempts at marsh restoration via removal of exotic/invasive plant species, we wanted to describe the current relationship between these plants and sediment nutrient pools. Extant stands (n=3 of each) of T. angustifolia, L. salicaria, and P. australis were sampled with porewater equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 24 publications
1
59
2
Order By: Relevance
“…In addition, these plants could take up significantly more N (both DON and DIN) than S. alterniflora, which is evidenced by our field experiment and greater N assimilation by introduced Phragmites. Numerous studies have shown that Phragmites demands in introduced Phragmites and S. alterniflora marsh zones Estuaries and Coasts (2010) 33:784-797>50% more N than the species it displaces in salt, brackish, and tidal fresh marshes (Templer et al 1998, Windham 2001, Windham and Ehrenfeld 2003, Windham and Meyerson 2003. The high affinity and greater uptake of N could reduce N availability in sediment porewater for the other species.…”
Section: Don Assimilationmentioning
confidence: 99%
“…In addition, these plants could take up significantly more N (both DON and DIN) than S. alterniflora, which is evidenced by our field experiment and greater N assimilation by introduced Phragmites. Numerous studies have shown that Phragmites demands in introduced Phragmites and S. alterniflora marsh zones Estuaries and Coasts (2010) 33:784-797>50% more N than the species it displaces in salt, brackish, and tidal fresh marshes (Templer et al 1998, Windham 2001, Windham and Ehrenfeld 2003, Windham and Meyerson 2003. The high affinity and greater uptake of N could reduce N availability in sediment porewater for the other species.…”
Section: Don Assimilationmentioning
confidence: 99%
“…Nitrogen cascading into riverine sediments from upwelling groundwater, may be attenuated in the hyporheic zone through immobilization (sorption, and plant and microbial uptake) (Howard-Williams et al 1982;Clarke 2002;Strauss and Lamberti 2002), and through reduction to N 2 gas by denitrification before the reactive N joins river flows (Pretty et al 2006;Krause et al 2009;Trimmer et al 2009;Stelzer et al 2011;Forshay and Dodson 2011;Harrison et al 2012). In addition to research looking at the influence of classic geomorphic features of rivers on nutrient cycling in riverine sediments, a number of researchers have also noted the importance of evaluating the influence of different vegetation types on nutrient cycling including those growing in riverbeds (Templer et al 1996;Wigand et al 2001;Clarke and Wharton 2001;Groffman et al 2005;Trimmer et al 2009;Lefebvre et al 2006;Forshay and Dodson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…3-10 cm below river bed) in the rooting zones of vegetation (Templer et al 1996;Wigand et al 2001;Groffman et al 2005;Forshay and Dodson 2011). However, the stimulation of the activity of microbes, including those responsible for NO 3 -attenuation, by vegetation may extend beyond typical rooting depths (from 5 to 12 cm) in the sediments: this possibility needs investigation to be able to account for sediment NO 3 -attenuation more accurately in and beyond the rooting depth.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have linked changes in nutrient cycling in estuarine oligohaline zones to nonindigenous plants (e.g. Posey et al 1993, Templer et al 1998, Meyerson et al 1999. In contrast, the effects of nonindigenous plants on nutrient cycling in lower (mesohaline and marine) estuary zones have not been reported.…”
Section: Introductionmentioning
confidence: 99%